Peak atrial longitudinal strain is predictive of atrial fibrillation in patients with chronic obstructive pulmonary disease and coronary artery disease. Issue 6 (10th May 2021) - Pavasini, Rita; Fabbri, Gioele; Fiorio, Alessio; Campana, Roberta; Passarini, Giulia; Verardi, Filippo Maria; Contoli, Marco; Campo, Gianluca
Abstract: Background: The peak atrial longitudinal strain (PALS) has been validated in the prediction of atrial fibrillation (AF) in the general population. If this finding can be applied to patients with chronic obstructive pulmonary disease (COPD) and concomitant coronary artery disease (CAD) is unknown. Methods and results: We analyzed two different study populations of patients with COPD and acute CAD in SCAP trial (Clinical trial.org identifier NCT02324660) and COPD and stable CAD in the NATHAN‐NEVER trial (clinical trial.org identifier NCT02519608). All patients enrolled underwent spirometry and clinical specialistic evaluation to test COPD diagnosis. During the index evaluation, all patients underwent echocardiography. The primary endpoint of the study was the occurrence of AF. Overall, 175 patients have been enrolled. PALS was significantly lower in patients with COPD compared to patients without COPD (26% ± 8% vs. 30% ± 8% for PALS4CV, P = .003). After a mean follow‐up of 49 ± 15 months, 26 patients experienced at least one episode of AF. At multivariable analysis, only PALS (HR: 0.92, 95% CI: 0.86‐0.98, P = .014) resulted as an independent predictor of AF in COPD patients with CAD, with the best cutoff value of 25.5% (sensitivity 87% and specificity 70%). Conclusion: The present study confirmed a high incidence of AF events in COPD patients and that PALS is altered and able to independently predict AF in a specific cohort of patients with CAD and COPD. This study points out the need to integrate PALS measurement in the echocardiographic workup of all COPD patients, to early identify those at high risk of AF development.